2022
DOI: 10.3390/ma15196822
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Surface Roughness and Hardness of 3D Printed Resins

Abstract: The effect of printing parameters on the surface characteristics of three-dimensional (3D)-printed denture base resins (DBRs) is neglected. Therefore, this study investigated the effect of printing orientation and post-curing time on the surface roughness and hardness. One conventional heat-polymerized (HP) resin and two 3D-printing resins (NextDent (ND) and ASIGA (AS)) were used to fabricate a total of 250-disc (10 × 2.5 mm) specimens. ND and AS specimens were printed with different orientations (0-, 45-, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…The graph is plotted between the composite's average surface roughness and printing orientation; the comparison of results is shown in Figure 3. Accordingly, the printing orientation of 0° exhibits a lower surface roughness value of 2.813 µm irrespective of the high MRR (146.43 mg/min) due to the presence of a single layer in an XY (horizontal) plane 38,39 and machined under optimized conditions, 40 while the printing orientation of 45° and 90° resulted in 4.709 µm and 3.986 µm, respectively. After machining under optimized conditions, the 45° printed composite attained a high roughness value of 4.709 µm attributed to overlapped printed layer steps between adjacent deposits.…”
Section: Resultsmentioning
confidence: 96%
“…The graph is plotted between the composite's average surface roughness and printing orientation; the comparison of results is shown in Figure 3. Accordingly, the printing orientation of 0° exhibits a lower surface roughness value of 2.813 µm irrespective of the high MRR (146.43 mg/min) due to the presence of a single layer in an XY (horizontal) plane 38,39 and machined under optimized conditions, 40 while the printing orientation of 45° and 90° resulted in 4.709 µm and 3.986 µm, respectively. After machining under optimized conditions, the 45° printed composite attained a high roughness value of 4.709 µm attributed to overlapped printed layer steps between adjacent deposits.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, the DLP and LCD with the imaging system of curing the entire layer at once had better performance in inhibiting the adherence of the C. Albicans. An existing study compares the surface roughness between two DLP techniques and the heat-polymerized material [ 35 ]. The study showed that the surface roughness did not have significant changes across the two DLP techniques when printing with different orientations and post-curing with different time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the current study used a different material than the mentioned study, and varied results were expected. Another similar study compared the surface roughness and hardness of a 3D-printed denture base fabricated with two different DLP machines at different orientations [ 35 ]. The results showed that the surface roughness was not affected by the different printers and orientations; however, the different DLP printers did make an impact on the surface hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of the silane coupling agent enhanced the affinity of the polymer and zirconia resin due to interfacial adhesion [ 28 ]. The selection of denture base material and resin is crucial to the denture longevity, as it is dependent on the surface characteristic and surface properties [ 29 ].…”
Section: Discussionmentioning
confidence: 99%